Проблемы бурения внутрипластовых угольных скважин необходимой глубины - Васильев, Л.М.; Демченко, В.С; Демченко, С.В. (Геотехническая механика, 2009)
В праці викладені фактори, які впливають на результат буріння довгих свердловин. Розглянуті умови, при яких свердловина не виходить за межі вугільного пласта. In this article the influencing factors on outcome of long well-boring are stated. The conditions are considered that the bore-well doesn't out behind coal-bed edge.